Nilai-Nilai Keimanan yang Terkandung dalam Buku Maaf Tuhan, Aku Hampir Menyerah Karya Alfialghazi - Sinta Rahmawati; Ayi Sobarna; Heru Pratikno (Bandung Conference Series: Islamic Education, 2022)
Abstract. The values of faith in a person will shape the character, behavior and mindset in accordance with the teachings of the Islamic Shari'ah, along with the times a person will be faced with various kinds of problems, one of the functions of education is that education can answer problems or problems that arise faced by a person, it is necessary to provide a solution to education that is in accordance with the times. Therefore, the researcher took the values of faith contained in the book Maaf Tuhan, Aku Hampir Menyerah by Alfialghazi as the focus of the research. This study uses a descriptive qualitative method with the type of content analysis. The primary data source was taken from the book Maaf Tuhan, Aku Hampir Menyerah by Alfialghazi, The secondary data source was obtained from journals on the internet. Data collection techniques, firstly primary data collection from primary reference sources through analysis, secondly seeking secondary data from journals on the internet and books. Data analysis technique using content analysis method. The purpose of this study is to describe the values of faith in the book Maaf Tuhan, Aku Hampir Menyerah by Alfialghazi in the form of meaning contained in the ideas and thoughts of Alfi Syahri Ramadhan. Based on research in the book Maaf Tuhan, Aku Hampir Menyerah by Alfialghazi, in this book there are values of faith, first, the value of faith in laughter and endeavor. Second, the value of Istiqomah faith. Third, the value of Husnuzan's faith. The four values of sincere faith. The content of his ideas is to link religious teachings with all things contained in life, but still in accordance with the purpose of faith, namely to build a strong and basic foundation in terms of religion. Abstrak. Nilai-nilai keimanan dalam diri seseorang akan membentuk karakter, perilaku dan pola pikir yang sesuai dengan ajaran syariat Islam, seiring dengan perkembangan zaman seseorang akan dihadapkan pada berbagai macam permasalahan, salah satu fungsi pendidikan adalah sebagai pendidikan dapat menjawab permasalahan atau permasalahan yang timbul yang dihadapi seseorang, maka perlu diberikan solusi pendidikan yang sesuai dengan perkembangan zaman. Oleh karena itu, peneliti mengambil nilai-nilai keimanan yang terdapat dalam buku Maaf Tuhan, Aku Hampir Menyerah karya Alfialghazi sebagai fokus penelitian. Penelitian ini menggunakan metode deskriptif kualitatif dengan tipe analisis isi. Sumber data primer diambil dari buku Maaf Tuhan, Aku Hampir Menyerah karya Alfialghazi, Sumber data sekunder diperoleh dari jurnal di internet. Teknik pengumpulan data, pertama pengumpulan data primer dari sumber referensi primer melalui analisis, kedua mencari data sekunder dari jurnal di internet dan buku. Teknik analisis data menggunakan metode analisis isi. Tujuan penelitian ini adalah mendeskripsikan nilai-nilai keimanan dalam buku Maaf Tuhan, Aku Hampir Menyerah karya Alfialghazi dalam bentuk makna yang terkandung dalam gagasan dan pemikiran Alfi Syahri Ramadhan. Berdasarkan penelitian dalam buku Maaf Tuhan, Aku Hampir Menyerah karya Alfialghazi, dalam buku ini terdapat nilai-nilai keimanan, pertama, nilai keimanan dalam tawa dan ikhtiar. Kedua, nilai iman Istiqomah. Ketiga, nilai keimanan Husnuzan. Empat nilai iman yang tulus. Isi pemikirannya adalah mengaitkan ajaran agama dengan segala hal yang terkandung dalam kehidupan, namun tetap sesuai dengan tujuan iman, yaitu membangun landasan yang kuat dan mendasar dalam hal agama.